Viral Immunofluorescence with Rift Valley Fever Virus Infected MEFs in a 96 Well Plate - Theresa Moser; Sara Cherry (Bio-Protocol, 2012)
Immunofluorescence is a method to detect viral infection in multiple types of host cells. This procedure can be adapted for both high-throughput and low-throughput assays for any virus for which there are antibodies available. Time of infection and virus multiplicity of infection (MOI) vary and should be optimized for each virus and host cell type. Here we give an example of viral immunofluorescence in a 96 well plate with a Rift Valley fever virus (RVFV, strain MP12) infection in mouse embryonic fibroblasts (MEF).